Involvement and performance of U9 soccer players in 7v7 and 5v5 matches during competition - Bergmann, F.; Meier, C.; Braksiek, M. (German Journal of Exercise and Sport Research, 2022)
The question of appropriate game formats for soccer competitions in childhood is intensively discussed in both research and practice. Therefore, the purpose of the present study was to compare under-9 (U9) soccer players` involvement and performance regarding on-the-ball decision-making and skill execution as well as off-the-ball support in "traditional" 7v7 and "modified" 5v5 game formats in a competitive context. A tournament with U9 soccer players (N = 43) was conducted where both 7v7 and 5v5 game formats were applied. The matches were analyzed using the Game Performance Assessment Instrument. The interrater reliability for decision-making and skill execution and appropriate support was good to excellent. Only fair coefficients were found for inappropriate support. In the 5v5 matches, a higher overall game involvement was found (d = 0.48). This higher involvement resulted from significantly more appropriate and inappropriate decisions as well as from significantly more efficient and inefficient skill executions. No differences were found in the overall game performance. The performance of executed skills was significantly better in the 5v5 game format (np2 = 0.102). Low-involved and low-performing players achieved greater benefits from the modified form in terms of a higher game involvement and a better performance. The 5v5 game format seems to offer advantages for soccer competitions in the U9 age group regarding game involvement and performance.